Effects of flaxseed, raw soybeans and calcium salts of fatty acids on apparent total tract digestibility, energy balance and milk fatty acid profile of transition cows - Gandra, J. R.; Mingoti, R. D.; Barletta, R. V.; Takiya, C. S.; Verdurico, L. C.; Freitas, J. E.; Paiva, P. G. [UNESP]; Jesus, E. F. [UNESP]; Calomeni, G. D.; Renno, F. P. (Cambridge Univ Press, 2016)
Oilseeds offer some protection to the access of ruminal microorganisms and may be an alternative to calcium salts of fatty acids (FA), which are not fully inert in the ruminal environment. This study aimed to evaluate the effects of different sources of FA supplementation on apparent total tract nutrient digestibility, milk yield and composition, and energy balance (EB) of cows during the transition period and early lactation. We compared diets rich in C18:2 and C18:3 FA. Multiparous Holstein cows were randomly assigned to receive one of the four diets: control (n=11); whole flaxseed (WF, n=10), 60 and 80 g/kg (diet dry matter (DM) basis) of WF during the prepartum and postpartum periods, respectively; whole raw soybeans (WS, n=10), 120 and 160 g/kg (diet DM basis) of WS during the prepartum and postpartum periods, respectively; and calcium salts of unsaturated fatty acids (CSFA, n=11), 24 and 32 g/kg (diet DM basis) of CSFA during the prepartum and postpartum periods, respectively. Dry cows fed WF had higher DM and net energy of lactation (NEL) intake than those fed WS or CSFA. The FA supplementation did not alter DM and NDF apparent total tract digestibility, dry cows fed WF exhibited greater NDF total tract digestion than cows fed WS or CSFA. Feeding WS instead of CSFA did not alter NEL intake and total tract digestion of nutrients, but increased milk fat yield and concentration. Calculated efficiency of milk yield was not altered by diets. FA supplementation increased EB during the postpartum period. Experimental diets increased long-chain FA (saturated and unsaturated FA) in milk. In addition, cows fed WS and CSFA had higher C18:1 trans-11 FA and C18:2 cis, and lower C18:3 FA in milk than those fed WF. Furthermore, cows fed CSFA had higher C18:1 trans-11 and cis-9, trans-11 FA than cows fed WS. Although supplemental C18:2 and C18:3 FA did not influence the milk yield of cows, they positively affected EB and increased unsaturated long-chain FA in milk fat.
Keywords: fatty acid; linoleic acid; linolenic acid; oilseed; unsaturated fatty acid